ANTIMYCOTIC ACTIVITY OF NONI JUICE AGAINST SEBORRHOEIC DERMATITIS - SAINI JASDEEP KAUR,; MHATRE BHAKTI,; MARAR THANKAMANI, (International Journal of Pharma and Bio Sciences, 2016)
Morinda citrifolia, commonly known as Noni, has been proven to be effective in curing a number of health problems and diseases. There have been several investigations in the past few decades demonstrating activity of Morinda citrifolia L in psoriasis. It has been found to possess anti-microbial properties as well. In order to determine its anti-mycotic activity, commercially available Noni juice was used in-vitro against Malassezia furfur, lipophilic yeast causing seborrhoeic dermatitis and other superficial skin infections. According to the anti-mycotic activity assay carried out using well diffusion method, the zone of an inhibition of Noni juice was compared to the zone of inhibition of few natural products and standard antidandruff shampoo. It was determined that Noni juice showed comparatively higher anti-mycotic activity, thus proving as an effective alternative against seborrhoeic dermatitis.